2020
DOI: 10.1097/j.pain.0000000000002145
|View full text |Cite
|
Sign up to set email alerts
|

Assessing reasons for decreased primary care access for individuals on prescribed opioids: an audit study

Abstract: Many primary care clinics are resistant to accept new patients taking prescription opioids for chronic pain. It is unclear how much of this practice is specific to individuals who may be perceived to have aberrant opioid use. This study sought to determine whether clinics are more or less willing to accept and prescribe opioids to patients depending on whether their history is more or less suggestive of aberrant opioid use by conducting an audit survey of primary care clinics in 9 states from May to July 2019.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Stigma has been amplified by the frequent misperception that continued opioid use indicates an opioid use disorder and by blaming patients with chronic pain for opioid-related harms. A lack of high-quality longitudinal data for opioid use, analgesia effectiveness and functional improvement, opioid misuse, and opioid reduction has perpetuated reductive policies, poor pain care, increased bias and stigma, increased health risks and mortality [1][2][3][4] , and fractured patient-clinician relationships and has created barriers to care 5,6 . For instance, some physicians may decline to accept new patients with existing opioid prescriptions.…”
mentioning
confidence: 99%
“…Stigma has been amplified by the frequent misperception that continued opioid use indicates an opioid use disorder and by blaming patients with chronic pain for opioid-related harms. A lack of high-quality longitudinal data for opioid use, analgesia effectiveness and functional improvement, opioid misuse, and opioid reduction has perpetuated reductive policies, poor pain care, increased bias and stigma, increased health risks and mortality [1][2][3][4] , and fractured patient-clinician relationships and has created barriers to care 5,6 . For instance, some physicians may decline to accept new patients with existing opioid prescriptions.…”
mentioning
confidence: 99%
“…OUD stigma is a barrier to pain treatment. 57 Anticipation of OUD stigma involves expecting that one's pain complaints will not be believed. 26 This may be particularly relevant for patients with nociplastic pain.…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 12 Physicians' time, reimbursement, clinic-specific policies, and lack of resources were cited as possible reasons for refusing to accept patients taking prescription opioids. 11 , 12 …”
Section: Context For the Case Studymentioning
confidence: 99%
“…10 Unfortunately, research studies have demonstrated reduced access to primary health care for patients receiving prescription opioids. 11,12 Physicians' time, reimbursement, clinicspecific policies, and lack of resources were cited as possible reasons for refusing to accept patients taking prescription opioids. 11,12 Building on the lessons learned from the ARPO collaboration, the Opioid Rapid Response Program (ORRP) was established as a national program in 2020.…”
mentioning
confidence: 99%